Cyclic homology of monogenic extensions in the noncommutative setting - Carboni, G. (2009)
We study the Hochschild and cyclic homology of noncommutative monogenic extensions. As an application we compute the Hochschild and cyclic homology of the rank 1 Hopf algebras introduced in [L. Krop, D. Radford, Finite dimensional Hopf algebras of rank 1 in characteristic 0, Journal of Algebra 302 (1) (2006) 214-230]. © 2008 Elsevier Inc. All rights reserved.